Strategi Bimbingan Konseling Penyuluhan Agama Islam Pra- Nikah - Muhamad Rudi Wijaya (Yayasan Literasi Sains Indonesia, 2022)
Marriage is no longer just a physical relationship but also an inner relationship. The provisions regarding marriage according to Islamic law are binding on every Muslim, and in marriage are contained ubudiyah values. A religious instructor is someone who has the goal of enlightening and enlightening the community who acts as a deterrent, companion and mediator for the community in Batanghari, East Lampung Regency, Lampung District. The role of religious counselors is to try to realize the hopes of the bride and groom to become a sakinah, mawwadah, warahmah family by providing marriage guidance with materials that are in accordance with Islamic teachings. The type of research in this research is field research. The research object that was taken by researchers to carry out activities was in one of the Offices of Religious Affairs (KUA) Batanghari District, East Lampung Regency, Lampung. Data collection techniques used are observation, structured interviews, and documentation. Data analysis used is qualitative analysis with deductive method. Researchers analyzed the validity of the data by using source triangulation. This study concludes that 1) the role of the ustadz in preventing family conflicts at the KUA Batanghari, East Lampung Regency, Lampung Regency is as a deterrent, companion and as a mediator. 2) The Islamic guidance and counseling methods used by religious educators are premarital counseling and family counseling.